If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p = 6p + 16 Reorder the terms: 2p = 16 + 6p Solving 2p = 16 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 2p + -6p = 16 + 6p + -6p Combine like terms: 2p + -6p = -4p -4p = 16 + 6p + -6p Combine like terms: 6p + -6p = 0 -4p = 16 + 0 -4p = 16 Divide each side by '-4'. p = -4 Simplifying p = -4
| 2a+2a=8 | | 5.5x+32=32 | | (-12)x=-144 | | 99(12)=9k | | 5+(14/2)=5+(n-3) | | 12+x=5x+4 | | 278+616= | | H(x)=-3x^4+21x^3-48x^2+36xfactor | | 14y+20y=120 | | x^4-x^3+12=0 | | 3-x+8+x-5x+x=360 | | 4x^3+3x=-2 | | h=-5t^2+8t | | 5+(14-2)=5+(n-3) | | 9x-14=6x+37 | | 2[1-3(x+2)]=x | | 90=15h | | -14=-5x+13 | | 14-2x+5=-2x+9 | | 7x(4-2)= | | 0.02(y-7)+0.10y=0.04y-0.09(10) | | 45g=720 | | -3(-6x-2)=-30 | | -23+x+28=x+5 | | X^2+47x+210=0 | | 5r+2=-1+4r | | 46.50n-15=5.25 | | 5x+14-2x=9+3(x+2) | | (5x-64)=3x | | -8(v*3)-7v=-4+10(1-v) | | 9k-21=3(k-7)+6k | | 25(35h)=40h |